AI-Based English Module for Accounting Students - Kurnia, Lely Indah; Setyawan, Bimo; Khoirunisa, Rizqi; Mustofa, Ahmad; Dja’far, Veri Hardinansyah; Purnomo, Subekhi Hadi (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2025)
Artificial Intelligence (AI) has significantly transformed education and language learning by creating more interactive, personalized, and adaptive learning environments. Within the field of English for Specific Purposes (ESP), especially for accounting students, there is an increasing need for learning modules that combine discipline-based content with advanced educational technology. However, existing resources remain limited and often fail to meet the specific linguistic and professional demands of vocational learners. This study aimed to design and evaluate an AI-based English module tailored to the needs of accounting students. Employing a Research and Development (R&D) approach using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation), the research involved need analysis, expert validation, small-group testing, and field implementation. The findings revealed that the module achieved a high feasibility rating from experts (87.2%), significantly improved students’ English achievement (from a pre-test mean of 62.4 to a post-test mean of 80.7, p < 0.05), and received positive responses from users. Most students reported improved comprehension of accounting terms, enhanced confidence in professional communication, and satisfaction with AI-integrated features such as chatbot interaction and speech recognition. These results indicate that the AI-based module is pedagogically effective, technologically interactive, and contextually relevant to vocational English education. Theoretically, this study contributes to ESP pedagogy, while practically, it offers a model for integrating AI-assisted learning in higher education contexts.